PERILAKU KOMUNIKASI DALAM PERJUDIAN SEPAK BOLA (Studi Pada Masyarakat Di Desa Lagundi Kecamatan Kambowa Kabupaten Buton Utara) - Sirajuddin, Endi Pamaran La Tarifu, (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2017)
ABSTRACTThe problems in this research are: (1) How is the communication behavior of society in doing soccer gambling in Lagundi Village, Kambowa Sub-district, North Buton Regency. (2) what factors influence the community's gambling behavior in Lagundi Village Kambowa Sub-district of North Buton Regency. The purpose of this research is to know: (1) to know the communication behavior of society in doing soccer gambling in Lagundi Village, Kambowa Sub-district, North Buton Regency, (2) to know what factors influence the community's gambling behavior in Lagundi Village Kambowa Sub-district of North Buton Regency. The benefits of research (1) may contribute to the development of communication science especially related to communication behavior, (2) become input for society not to do soccer gambling, (3) as comparison and reference for next researcher.This research was conducted at Lagundi Village, Kambowa Sub-district, North Buton Regency. Informants in this study consists of 9 people, namely residents who have a population in the village Lagundi. Data collection was done by interview and observation. Data analysis used qualitative descriptive analysis. The results showed that: 1) the soccer gambling behavior in Lagundi Village Kambowa Sub-district of North Buton Regency refers to the desire within each performer to do the ball gambling each week and the habit of them to do the soccer gambling in order to get a big advantage 2) the behavior of soccer Influenced by social factors, economics, situational, learning factors, perceptions about the chances of victory and perceptual factors of skills.Â Keywords: Â Perilaku Komunikasi, Masyarakat, Perjudian Sepakbola